Influence of the radioactive concentration of the in vitro stability of Tc-99m(Sn)-pyrophosphate - JURIJ L. VUCINA (Journal of the Serbian Chemical Society, 1999)
The in vitro stability of 99mTc(Sn)-pyrophosphate solution was examined in dependence on the preparation conditions of the samples, the radioactive concentration of 99mTc in the kit and the time elapsed after labeling. The samples without any protection are highly unstable. The formation of 99mTc-pertechnetate does not depend on the radioactive concentration. Nitrogen purging provides protection in the case of low radioactive concentrations (37 MBq 99mTc/ml) but exhibits no effect at higher concentrations. The best stabilization was achieved by using ascorbic acid. A concentration of 60 µg/ml keeps the content of 99mTc-pertechnetate below 1% during six hours after labeling, even in solutions of high readioactive concentrations (740-814 MBq/ml). Gentisic acid is less effective. Concentrations about ten times higher than required using ascorbic acid are needed to keep the content of 99mTc-pertechnetate below 5% during six hours.